Concerning the Integration of the Wcc and the Imc (The ecumenical review, 1956)
The mandate of the WCC-IMC Joint Committee, as formulated at König-stein in February 1954, includes the obligation to “study the advantages, dis-advantages and implications of a full integration of the International Missionary Council and the World Council of Churches.” The Committee at its meeting on July 20–23, 1956, returned to the consideration of this question and adopted the following statement for submission to the WCC and the IMC. The Central Committee of the WCC authorised the use of this statement as an interpretation of the present stage of discussion of the question.